The effect of counseling with a positive approach on anxiety about giving birth to an Infant with Anomalies in pregnant mothers over 35 years of age - Hadis Jalilvand; Mojghan Mokhtari Zanjani; Taraneh Emamgholi Khooshehchin (Preventive Care in Nursing and Midwifery Journal)
Background: Currently, a significant number of women are becoming pregnant after the age of 35. Since advanced maternal age is recognized as a risk factor for adverse pregnancy outcomes and fetal complications, there is a heightened potential for increased anxiety and worry among those who become pregnant at older age. Prenatal counseling can play an important role in reducing anxiety and psychological distress, while also promoting the physical and mental well-being of expectant mothers. Objectives: The present study aimed to determine the effect of positive counseling on anxiety concerning giving birth to an infant with anomalies in pregnant women over 35 years of age. Methods: This randomized clinical trial was conducted on 46 pregnant mothers over 35. Participants were conveniently recruited and then randomly assigned to either the experimental or control group using block randomization. The study instrument was the Pregnancy-Related Anxiety Questionnaire (PRAQ; Vanden Berg, 1989). The experimental group received positive counseling in eight 70-90-minute virtual sessions. Data were analyzed using the Chi-square test, independent samples t-test, and covariance (ANCOVA) analysis in SPSS version 22. Results: The mean scores of anxieties concerning giving birth to an infant with anomalies before the intervention were 16.30 (6.47) in the experimental group and 12.13 (6.31) in the control group. An independent samples t-test revealed a statistically significant difference between the mean pretest scores of the two groups (p = 0.032). After the intervention, the mean scores of anxieties concerning giving birth to an infant with anomalies were 8.56 (4.65) in the experimental group and 13.34 (6.47) in the control group. An ANCOVA demonstrated a statistically significant difference between the mean post-test scores of the two groups (p < 0.001). Conclusion: Positive counseling reduces anxiety concerning giving birth to an infant with anomalies in pregnant women over 35 years of age.